Ceramic coated diaphragm and preparation method thereof, and secondary battery

By introducing organic polymers into the ceramic coating and controlling the hot pressing conditions, the organic compound adhesive film is formed, which solves the problems of ion transport performance and peel strength of the ceramic coating after hot pressing, and improves the cycle stability and safety of the battery sex.

CN118712657BActive Publication Date: 2025-02-07SINOMA LITHIUM BATTERY SEPARATOR CO LTD

Patent Information

Application Number
CN202411193909.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-28
Publication Date
2025-02-07
Estimated Expiration
2044-08-28

AI Technical Summary

Technical Problem

During the hot pressing process of ceramic-coated separator, organic matter in the ceramic coating will dissolve and form a covering, affecting the ion transport performance and peel strength of the separator, and thus affecting the cycle stability and safety of the battery.

Method used

By introducing organic polymer into the ceramic coating and processing under specific hot pressing conditions, an organic adhesive film is formed on the surface of the ceramic coating, with the coverage ratio controlled within 0-5%, and the peel strength after hot pressing is 20gf /15mm or above.

Benefits of technology

The high ion transport performance and peel strength of the ceramic coated separator after hot pressing are achieved, and the cycle stability and safety performance of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118712657B_ABST
    Figure CN118712657B_ABST
Patent Text Reader

Abstract

The present invention discloses a ceramic coated diaphragm and a preparation method thereof, and a secondary battery. The ceramic coated diaphragm comprises a substrate layer and a ceramic coating, wherein the ceramic coating comprises ceramic particles, a binder polymer and an organic high molecular polymer. Under hot pressing conditions of a temperature of 90°C and a pressure of 4MPa, an organic film is formed on the surface of the ceramic coating after hot pressing, wherein the coverage of the organic film is 0-5%, the value-added permeability per unit coating thickness after hot pressing is 0-15s / 100cc, and the peel strength after hot pressing is above 20gf / 15mm. The separator designed by the present invention still has high peel strength and ion permeability after hot pressing, the internal resistance of the battery is reduced, and the cycle and capacity are correspondingly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of secondary battery diaphragms, and in particular relates to a ceramic coated diaphragm and a preparation method thereof, and a secondary battery. Background Art

[0002] Aqueous ceramic coated diaphragms are formed by uniformly coating ceramic materials or ceramic composite materials on the surface of the substrate of the battery diaphragm through an aqueous coating process, thereby forming a composite diaphragm with ion conductivity, electronic insulation, high mechanical strength, and high heat resistance. Aqueous ceramic coated diaphragms are used in batteries and have the following advantages over common organic polymer coated diaphragms: First, aqueous ceramic coated diaphragms can significantly improve the ion conductivity of the battery. The good ion permeability of the ceramic coating layer makes the ion migration of the battery faster and more efficient during the charging and discharging process, thereby improving the battery's charging and discharging performance and cycle stability; secondly, the ceramic coating layer can inhibit the shrinkage of the diaphragm at high temperatures, effectively prevent internal short circuits and explosions in the battery, and improve the safety of the battery; finally, the aqueous ceramic coating process is relatively simple and low in cost. In summary, aqueous ceramic coated diaphragms can achieve higher cost-effectiveness in the large-scale production of batteries, which is very helpful in reducing the overall cost of batteries.

[0003] However, despite the above advantages of using water-based ceramic coated diaphragms in batteries, the existing technology still faces some problems in the practical application of water-based ceramic coated diaphragms. The mechanical strength of ceramic particles and substrates is relatively low, which may affect the long-term cycle stability of the battery. In order to ensure that the ceramic particles have high mechanical strength and good coating adhesion, polymers are usually added, but the introduction of polymers will affect the migration rate of ions, which is more prominent in multi-layer coating. Summary of the invention

[0004] After an organic high molecular polymer is introduced into the ceramic coating of the ceramic coated diaphragm, how to better maintain the ion transmission performance of the ceramic coated diaphragm after hot pressing and improve the liquid storage capacity during the battery filling process is a technical problem to be solved by the technical solution of the present invention.

[0005] In the first aspect, the present invention provides a ceramic coated diaphragm, comprising a substrate layer and a ceramic coating, wherein the ceramic coating comprises ceramic particles, a binder polymer and an organic high molecular polymer. Under hot pressing conditions at a temperature of 90°C and a pressure of 4MPa, an organic film is formed on the surface of the ceramic coating after hot pressing, and the coverage of the organic film is 0-5%. The value-added permeability per unit coating thickness after hot pressing is 0-15s / 100cc, and the peel strength after hot pressing is above 20gf / 15mm.

[0006] In a second aspect, the present invention provides a method for preparing a ceramic coated diaphragm, comprising: applying a ceramic coating slurry to a surface of at least one side of a substrate layer to obtain a substrate layer coated with a ceramic coating, and drying the substrate layer coated with the ceramic coating to obtain a ceramic coated diaphragm. The method for preparing the ceramic coating slurry comprises:

[0007] Adding organic high molecular polymer powder into the solvent in two batches to obtain thickener slurry, wherein the mass ratio of the organic high molecular polymer powder before and after is 2:5-2:3;

[0008] adding ceramic particles into a solvent to obtain a ceramic particle slurry;

[0009] Mixing the thickener slurry and the ceramic particle slurry to obtain a thickening slurry;

[0010] Below 65°C, the thickening slurry is conveyed to the grinder by a feed pump, and the semi-finished slurry is obtained by grinding the grinder. The grinding speed is 500-800rpm, the diameter of the pick is 0.5-0.8mm, the feed pump speed is 600-1000rpm, and the ratio of the feed pump speed to the grinder speed is 1.1-1.6;

[0011] After the temperature of the semi-finished product slurry returns to room temperature, a binder polymer and a wetting agent are added, and the mixture is evenly mixed to obtain a ceramic coating slurry;

[0012] During the coating process, the size of the scraper leakage accounts for 40-50% of the scraper size, and the angle of the scraper and the angle of the cover plate are maintained at 0-45°. The tension applied to the base film per unit thickness and unit width is 2.5-5N / (m·μm). During the coating process, the ratio of the coating roller speed to the coating vehicle speed is between 0.8-1.2;

[0013] The drying process controls the oven temperature to 50-80°C, the pressure inside the oven to 0-0.03Mpa, the oven temperature is heated in sections, and the temperature difference between two adjacent sections of the oven is ≤5°C.

[0014] In a third aspect, the present invention provides a secondary battery comprising the ceramic coated separator described above.

[0015] Compared with the prior art, the present invention has the following beneficial effects:

[0016] The isolation film designed by the present invention still has high peel strength and ion permeability after hot pressing, the internal resistance of the battery is reduced, and the cycle and capacity are correspondingly improved. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 This is a scanning electron microscope image of the coated diaphragm obtained in Example 1 before hot pressing;

[0018] Figure 2 This is a scanning electron microscope image of the coated diaphragm obtained in Example 1 after hot pressing;

[0019] Figure 3 For Figure 2 The SEM image of the area covered by the organic film is shown in the figure. Figure 3 The areas circled by red coils numbered 1, 2, 3, 4, and 5 are the areas covered by the film. DETAILED DESCRIPTION

[0020] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.

[0021] A ceramic coated diaphragm comprises a substrate layer and a ceramic coating, wherein the ceramic coating comprises ceramic particles and an organic high molecular polymer. Under hot pressing conditions at a temperature of 90°C and a pressure of 4MPa, the organic film coverage on the surface of the ceramic coating after hot pressing is 0-5%, such as 0, 1%, 2%, 3%, 4%, 5%; the value-added permeability per unit coating thickness after hot pressing is 0-15s / 100cc, such as 0, 3s / 100cc, 5s / 100cc, 8s / 100cc, 10s / 100cc, 15s / 100cc; the peel strength after hot pressing is above 20gf / 15mm, such as 30gf / 15mm, 40gf / 15mm, 45gf / 15mm...

[0022] Secondary battery cells need to go through a hot pressing process during assembly. The present application found that after the hot pressing process, the organic matter in the ceramic coating will dissolve to the surface of the ceramic particles to form a coating, which will affect the ion transmission capacity of the ceramic coating after the hot pressing process, and then affect the liquid injection capacity of the battery cell, while increasing the ion migration resistance during the battery charge and discharge process. At the same time, the present application also found that the precipitation of organic matter will lead to a decrease in the organic content near the contact surface between the base film and the ceramic coating, thereby affecting the peel strength of the coating. The above phenomenon discovered by the present application is more obvious when other organic high molecular polymers besides the binder polymer are added to the ceramic coating, and the impact on the performance of the diaphragm is more significant.

[0023] The present application further finds that after applying specific hot pressing conditions to the diaphragm, the organic matter in the ceramic coating will form an organic film on the outer surface of the diaphragm, covering the outer surface of the ceramic coating. By measuring the coverage of the organic film after specific hot pressing conditions, some characteristics of organic polymers and ceramic particles in the ceramic coating can be reflected, including but not limited to the distribution mode of ceramic particles in the coating, the distribution mode of organic polymers in the thickness direction of the coating, and the distribution relationship between organic polymers and ceramic particles. These characteristics are quantitatively expressed by "coverage" after hot pressing. The present application finds that by limiting the coverage within a certain range, the diaphragm after hot pressing can show better ion transmission performance and better peeling strength. When the coverage is greater than 5%, the ion transmission efficiency of the ceramic coating of the diaphragm after hot pressing is low, and the coating peeling strength is small, which will adversely affect the charge and discharge performance and safety performance of the battery cell. The lower the coverage of the diaphragm, the more conducive it is for the diaphragm to show good ion conductivity and good peeling strength in the battery cell. The ideal lower limit of coverage is 0%, but the actual lower limit is 0.2%.

[0024] Coverage can be characterized in the following ways:

[0025] Take the diaphragm under the above hot pressing conditions, observe the film coverage by scanning electron microscope, take pictures at a magnification of 10k, and calculate the total area S of the diaphragm within the field of view by Image software. 总 and the area covered by the film S 胶膜 , then the coverage is calculated as S 胶膜 / S 总 The type of scanning electron microscope is not particularly limited in this application, and this embodiment uses a ZEISS SIGMA 300 scanning electron microscope. The film appears fuzzy, pasty or gel-like in the electron microscope image, occupying a certain area continuously or discontinuously.

[0026] In the present invention, there is no particular limitation on the base film, and it can be any material known in the art that can be used as a diaphragm base film, such as a coated or uncoated polyolefin base film, a coated or uncoated non-woven base film, and a coated or uncoated electrospinning base film, preferably a coated or uncoated polyolefin base film; the polyolefin base film can be a single-layer or multi-layer polyethylene or polypropylene base film. From the perspective of film-forming performance, polyethylene and copolymers are preferred. Polyethylene can be obtained by one-step polymerization or multi-step polymerization. The molecular weight of the polyethylene is 500,000-4 million, such as 500,000, 1 million, 1.5 million, 2 million, 2.5 million, 3 million, 3.5 million and 4 million, preferably 600,000-3 million, particularly preferably 800,000-3 million, and the particle size of the polyethylene is ≤1000μm, such as 1000μm, 900μm, 800μm, 700μm, 600μm, 500μm and 400μm.

[0027] The present invention does not impose any particular limitation on the production process of the base film, and can adopt dry uniaxial stretching, biaxial synchronous or asynchronous stretching, and wet biaxial synchronous or asynchronous stretching. Preferably, the base film is prepared by wet biaxial synchronous or asynchronous stretching.

[0028] In the present invention, the thickness of the base film is 1-30μm, such as 1μm, 3μm, 5μm, 8μm, 10μm, 13μm, 15μm, 18μm, 20μm, 22μm, 25μm and 30μm, preferably 3-20μm; the porosity of the base film is 10-70%, such as 10%, 15%, 20%, 25%, 30%, 40%, 50%, 60% and 70%, preferably 20-60%.

[0029] In the present invention, the ceramic coating comprises 82-99 parts by weight of ceramic particles, 1.5-7 parts by weight of binder polymer and 0.1-1.5 parts by weight of organic high molecular polymer.

[0030] In the present invention, the thickness of the ceramic coating is 0.5-10 μm, such as 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm and 10 μm.

[0031] In the present invention, the particle size D50 of the ceramic particles is 0.01 μm-2 μm, such as 0.01 μm, 0.05 μm, 0.1 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, and the specific surface area is 0-30 m 2 / g, such as 2m 2 / g, 5m 2 / g, 8m 2 / g, 10m 2 / g, 15m2 / g, 20m 2 / g, 25m 2 / g and 30m 2 / g, preferably 2-20m 2 / g, more preferably 3-18m 2 / g, the specific surface area of ​​ceramic particles is within the above range, which can increase the surface energy of the particles and improve the wettability of the electrolyte in the diaphragm, thereby improving the cycle performance of the battery. In addition, it can also improve the cohesion between slurry particles and the fluidity of the slurry, and reduce the problem of uneven coating due to high-speed shearing during the coating process; at the same time, the specific surface area of ​​the ceramic particles is controlled within this range, and the water content in the diaphragm is effectively controlled, thereby inhibiting the side reaction of water in the electrolyte and improving the cycle performance of the battery.

[0032] Examples of ceramic particles include oxide particles such as silicon dioxide (SiO2), aluminum oxide (Al2O3), magnesium oxide (MgO), zirconium oxide (ZrO2), titanium oxide (TiO2), calcium oxide (CaO), nitride particles such as boehmite (ALOOH), aluminum nitride (AlN), boron nitride (BN), insoluble ion crystalline particles such as barium sulfate (BaSO4), calcium fluoride (CaF2) and barium fluoride (BaF2), and barium titanate (BaTiO3) particles with high dielectric constant and low dielectric loss. One of the above particles can be selected, or two or more particles in any proportion. Among these particles, oxide particles are preferred in consideration of stability and potential in the electrolyte. Alumina, boehmite, magnesium oxide, and silicon dioxide are preferred, and aluminum oxide and boehmite are particularly preferred. Aluminum oxide and boehmite can neutralize hydrogen fluoride, a byproduct formed by the reaction of electrolyte and water, and inhibit voltage drop, thereby improving the battery's high-temperature charge storage capacity and room-temperature cycle capacity.

[0033] There is no particular restriction on the shape of the ceramic particles, such as plate-like, flaky, needle-like, columnar, spherical, polyhedral, block-like, etc., and a combination of ceramic particles having the above shapes can also be used. From the perspective of improving permeability, plate-like, block-like, polyhedral, and columnar shapes with multiple faces are preferred.

[0034] The ceramic particles may also contain particles with ion transfer ability, thereby improving the ion conductivity. The particles with ion transfer ability are selected from any one of the following or a mixture of at least two: lithium phosphate, lithium titanium phosphate, lithium aluminum titanium phosphate, lithium nitride, lithium carbonate, lithium chloride, lithium sulfide and lithium hexafluorophosphate.

[0035] In the present invention, the binder polymer comprises one or more of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, acrylic acid and its derivative copolymers, acrylamide and its derivative copolymers, preferably polyvinylidene fluoride and / or acrylic resin. The binder polymer mainly plays a role in maintaining the mechanical strength of the porous membrane, maintaining the toughness of the porous membrane, and inhibiting the non-conductive particles from falling off the porous membrane during the winding process of the ion battery.

[0036] The binder polymer should have stable electrochemical properties, which are mainly manifested in that, within a voltage range of 1-5V, there are no other redox current peaks except for the electrode lithium desorption / insertion redox peak.

[0037] In the present invention, the organic high molecular polymer is a polysaccharide natural high molecular weight polymer or compound and / or a cellulose semi-synthetic high molecular weight compound. In view of improving the dispersibility of the non-conductive particles, the organic high molecular weight polymer is preferably a cellulose semi-synthetic high molecular weight compound.

[0038] In the present invention, considering the dispersibility of non-conductive particles in water, the etherification degree of the cellulose semi-synthetic polymer compound is preferably selected to be 0.5-1.2, such as 0.5, 0.7, 0.9, 1.1, 1.2, preferably 0.7-1.0, and the etherification degree refers to the degree of substitution of the hydroxyl groups (3) of each anhydrous glucose unit in cellulose by substituents such as carboxymethyl. The number average molecular weight of the cellulose semi-synthetic polymer compound is 75000-95000, such as 75000, 80000, 90000 and 95000, preferably 78000-93000, and particularly preferably 80000-9000. The number average molecular weight of the polymer mainly affects the fluidity of the slurry and thus affects the stability of the slurry and the coating effect. By controlling the number average molecular weight of the polymer in the above range, the stability of the slurry and the uniformity of the coating during coating are improved.

[0039] In the present invention, the organic high molecular polymer has a thermal melting ratio of less than 20% at a mass concentration of 4%, and a thermal elastic recovery modulus of more than 85%.

[0040] Melt ratio = (initial viscosity - viscosity after heating) / initial viscosity

[0041] Thermoelastic recovery modulus = (initial viscosity - viscosity after heating and recovery to room temperature) / initial viscosity

[0042] The heating temperature is 60°C and the heating time is 1h. For the temperature rise caused by heat generated during high shear processes such as planetary stirring, grinding, and high-speed dispersion, it is usually necessary to pass cooling water into the tank. The heat-to-melt ratio is within the above range, which reduces the energy consumption of the equipment during the pulping process. At the same time, it can reduce the problem of uneven distribution of inorganic particles caused by rapid evaporation of water during baking after coating.

[0043] In order to obtain the isolation membrane designed by the present invention, the present invention provides a method for preparing a ceramic coated membrane. However, the isolation membrane designed by the present invention is not limited to being prepared by the preparation method provided by the present invention.

[0044] A method for preparing a ceramic coated diaphragm comprises applying a ceramic coating slurry onto the surface of at least one side of a substrate layer to obtain a substrate layer coated with a ceramic coating, and drying the substrate layer coated with the ceramic coating to obtain a ceramic coated diaphragm. The method for preparing the ceramic coating slurry comprises:

[0045] The organic high molecular polymer powder is added to the solvent to obtain a thickener slurry; more specifically, 90-99 parts by weight (such as 90 parts by weight, 93 parts by weight, 95 parts by weight, and 99 parts by weight) of the solvent is introduced into the stirring tank, the anchor paddle speed is set to 25rpm-40rpm (such as 25rpm, 30rpm, 35rpm, and 40rpm), the anchor paddle speed is turned on, and 1-10 parts by weight (such as 1 part by weight, 3 parts by weight, 5 parts by weight, 7 parts by weight, and 10 parts by weight) of the high molecular polymer powder is slowly added in two times (the mass of the high molecular polymer added in the first time is equal to the mass of the high molecular polymer added in the second time); The mass ratio of the sub-polymer is 2:5-2:3), after adding the first batch of powder, turn on the dispersion disk, the dispersion disk speed is 1000rpm-1300rpm (for example, it can be 1000rpm, 1100rpm, 1200rpm and 1300rpm), the stirring time is 5min-20min (for example, it can be 5min, 10min, 15min and 20min), add the second batch of powder, maintain the above-mentioned anchor paddle speed and dispersion disk speed unchanged, continue stirring for 15-30min (for example, it can be 15min, 20min, 25min and 30min) to obtain the thickener slurry.

[0046] Ceramic particles are added to a solvent to obtain a ceramic particle slurry; more specifically, 50-60 parts by weight, such as 50 parts by weight, 53 parts by weight, 57 parts by weight and 60 parts by weight of a solvent are injected into a double planetary stirring tank, and 32-38 parts by weight, such as 32 parts by weight, 35 parts by weight and 38 parts by weight of ceramic particles are slowly added, the speed of the anchor paddle in the double planetary stirring tank is 20rpm-30rpm, such as 20rpm, 25rpm and 30rpm, the speed of the dispersion disk is 800rpm-1500rpm, such as 800rpm, 1000rpm, 1200rpm and 1500rpm, the stirring time is 10min-20min, such as 10min, 12min, 15min and 20min, to obtain a ceramic particle slurry.

[0047] The thickener slurry and the ceramic particle slurry are mixed to obtain a thickening slurry; more specifically, 5-15 parts by weight, such as 5 parts by weight, 10 parts by weight and 15 parts by weight of the thickener slurry are added to the ceramic particle slurry, the anchor paddle speed in the double planetary stirring tank is 20rpm-30rpm, such as 20rpm, 25rpm and 30rpm, the dispersion disk speed is 1000rpm-1300rpm, such as 1000rpm, 1100rpm, 1200rpm and 1300rpm, the stirring time is 10min-20min, such as 10min, 15min and 20min, to obtain a thickening slurry.

[0048] Below 65° C., the thickening slurry is conveyed to a grinder by a feed pump, and the semi-finished slurry is obtained by grinding the grinder, the grinding machine speed is 500-800 rpm, such as 500 rpm, 600 rpm, 700 rpm and 800 rpm, the pick bead diameter is 0.5-0.8 mm, such as 0.5 mm, 0.6 mm, 0.7 mm and 0.8 mm, the feed pump speed is 600-1000 rpm, such as 600 rpm, 700 rpm, 800 rpm, 900 rpm and 1000 rpm, and the ratio of the feed pump speed to the grinder speed is 1.1-1.6, such as 1.1, 1.2, 1.3, 1.4, 1.5 and 1.6;

[0049] After the temperature of the semi-finished slurry is restored to room temperature, a binder polymer and a wetting agent are added, wherein the amount of the binder polymer added is 2-10 parts by weight, such as 2 parts by weight, 5 parts by weight and 10 parts by weight, and the amount of the wetting agent added is 0.03-0.2 parts by weight, such as 0.03 parts by weight, 0.05 parts by weight, 0.1 parts by weight, 0.15 parts by weight and 0.2 parts by weight. After uniform mixing, preferably at a stirring speed of 10rpm-50rpm, such as 10rpm, 20rpm, 30rpm, 40rpm and 50rpm, stirring for 15-50min, such as 15min, 20min, 25min, 30min, 40min and 50min, to obtain a ceramic coating slurry;

[0050] During the coating process, the size of the scraper leakage accounts for 40-50% of the scraper size, such as 40%, 45%, and 50%, and the angle of the scraper and the cover plate is maintained at 0-45°, specifically 3°, 10°, 15°, 20°, 25°, 30°, 35°, 40°, and 45°. The tension applied to the base film per unit thickness and unit width is 2.5-5N / (m·μm), specifically 2.5N / (m·μm), 3N / (m·μm), 3.5N / (m·μm), 4N / (m·μm), 4.5N / (m·μm), and 5N / (m·μm). During the coating process, the ratio of the coating roller speed to the coating vehicle speed is between 0.8-1.2, specifically 0.8, 0.9, 1.0, 1.1, and 1.2;

[0051] The drying process controls the oven temperature to 50-80°C, specifically 50°C, 60°C, 70°C and 80°C, the pressure in the oven is 0-0.03Mpa, specifically 0, 0.01Mpa, 0.02Mpa and 0.03Mpa, the oven temperature is heated in sections, and the temperature difference between two adjacent oven sections is ≤5°C, specifically 5°C, 4°C, 3°C, 2°C, 1°C and 0°C.

[0052] In the present invention, the pH of the ceramic coating slurry is 7-11, specifically 7, 8, 9, 10, 11, preferably 7.5-9.5; the viscosity is 5-200 mpa·s, specifically 5 mpa·s, 10 mpa·s, 30 mpa·s, 50 mpa·s, 100 mpa·s, 150 mpa·s and 200 mpa·s, preferably 10-130 mpa·s; more preferably 60-80 mpa·s; the slurry volume average particle size D50 is 0.01-2.5 μm, Specifically, it can be 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 1.5μm, 2μm and 2.5μm, preferably 0.1-1.2μm, and more preferably 0.8-1μm; the average value of the absolute value of the Zeta potential is 0.025-0.3V, specifically 0.025V, 0.05V, 0.07V, 0.1V, 0.15V, 0.2V, 0.25V and 0.3V, preferably 0.035-0.1V, and more preferably 0.07-0.1V.

[0053] The present invention controls the thermoelastic recovery modulus and heat-melt ratio of the polymer to enable it to have a higher thermoelastic recovery ability, which can reduce the influence of the temperature increase caused by the heat generated by high-speed shear and particle impact during the pulping and coating process on the slurry, thereby ensuring the stability of the slurry and the uniformity of the coating during the coating process. At the same time, there is no need to inject cooling water into the tank to cool the slurry, which reduces the energy consumption in the pulping process. In addition, during the drying and molding process, the slurry has high elasticity, which avoids the problem of uneven distribution of binders and polymers caused by too fast drying rate. The addition and regulation of ceramic particles, binder polymers, and organic polymers control the grinding machine pick beads, rotation speed, and feed pump speed in the pulping process within a certain range to prevent the stability of the semi-finished slurry from being destroyed during high-speed shearing. At the same time, it also reduces the problem of particle aggregation caused by charge instability after the addition of binder polymer particles, thereby ensuring that the ceramic particles, organic polymers, and binder polymers form a uniform and stable slurry system. On the other hand, by controlling the tension matching during the coating process of substrates of different thicknesses, the substrate can show better toughness and ductility, prevent the base film from shrinking after excessive stretching during the coating and drying process, and the coating has poor adhesion. In addition, the control of the scraper size, cover angle, and gravure roller and coating vehicle speed ratio in the gravure roller can ensure that the slurry is evenly distributed in the gravure roller texture during the coating process, and the ceramic particles are more densely accumulated after coating, which is conducive to improving the heat resistance of the diaphragm and the safety performance of the battery. By matching the oven temperature, the temperature difference between the ovens, and the wind field in the oven, the drying rate of each component in the coating is balanced, and the coating cracking and excessive floating of the binder caused by the drying rate being too fast are prevented, so that the ceramic particles are evenly spread on the surface of the base film. Through the above control points, the prepared diaphragm can have an organic film coverage of 0-5% after hot pressing, an increase in the air permeability per unit coating thickness after hot pressing of 0-15s / 100cc, and a peel strength of more than 20gf / 15mm after hot pressing.

[0054] A secondary battery comprises the ceramic coated separator described above.

[0055] The present invention is described in detail below by way of examples.

[0056] Example 1

[0057] Inorganic coating slurry preparation:

[0058] (1) Preparation of thickening stock: 97 kg of ultrapure water was introduced into a stirring tank, the speed of the anchor paddle was set to 20 rpm, and the anchor paddle speed was turned on. 1.2 kg of thickener sodium carboxymethyl cellulose (etherification degree 0.91, number average molecular weight 85232) powder was slowly added. After the addition was completed, the dispersion disk was turned on, the dispersion disk speed was 1200 rpm, and the stirring time was 20 min. Then, 1.8 kg of thickener sodium carboxymethyl cellulose powder was added, and the dispersion disk was turned on again. The dispersion disk speed was 1200 rpm and the stirring time was 40 min to obtain 100 kg of thickener stock;

[0059] (2) 145 kg of ultrapure water was pumped into a double planetary stirring tank, and 100 kg of alumina with a volume average particle size D50 of 0.841 μm was slowly added; the speed of the double planetary anchor impeller was 20 rpm, the speed of the dispersion disk was 1000 rpm, and the stirring time was 10 min to obtain alumina slurry;

[0060] (3) adding 26.67 kg of thickener slurry to the above alumina slurry, and using the double planetary stirring anchor impeller speed, dispersion disk speed, and stirring time in step (2) to obtain a thickening slurry;

[0061] (4) The thickening slurry is passed through a grinder with a feed pump speed of 800 rpm, a grinder speed of 500 rpm, and a grinder bead size of 0.72 mm to obtain a semi-finished slurry. After the semi-finished slurry temperature returns to room temperature, 8.89 kg of binder acrylate (Ruiong; 900B) and 0.13 kg of wetting agent (Guangdong Guoyuanxing TEGO202E) are added and stirred for 30 minutes. The stirring speed is controlled at 20 rpm to obtain a finished slurry.

[0062] The pH value of the obtained finished slurry is 8.68, the viscosity is 56.4 mpa·s, and the volume average particle size D50 of the slurry is 0.833 μm.

[0063] Preparation of isolation film:

[0064] A polyethylene base film with a thickness of 9 μm (produced by Zhongcai Lithium Membrane Co., Ltd., with an air permeability of 126 s / 100 cc) was used; a coating tension of 4 N / (m·μm) was used, the size of the scraper leakage accounted for 47% of the scraper size, the angle of the scraper to the cover plate angle was 20°, the ratio of the gravure roller speed to the coating vehicle speed was 0.9, the prepared finished slurry was coated on one side of the base film, the prepared coated isolation film was dried in an oven, the drying temperature was 65°C, the temperature difference between adjacent ovens was 3°C, the oven pressure difference was 0.01 MPa, and a coated film was obtained.

[0065] The peel strength of the diaphragm is 179N / m, the coating thickness is 3.1μm, the air permeability of the coating per unit thickness is 5s / 100cc / μm, the thermal shrinkage rates at 130℃, 1hMD, and TD are 1.9 and 1.2 respectively, the film coverage after hot pressing is 0.3%, and the added value of the air permeability of the diaphragm coating thickness after hot pressing is 3s / 100cc / μm. Figure 1 This is a scanning electron microscope image of the coated diaphragm obtained in Example 1 before hot pressing. Figure 2 This is a scanning electron microscope image of the coated diaphragm obtained in Example 1 after hot pressing. Figure 3 For Figure 2 The film area is marked on the scanning electron microscope image shown, such as the area circled in red in the figure.

[0066] Embodiment 2-5

[0067] The specific raw materials, preparation parameters, isolation membrane parameters and properties of the remaining embodiments are shown in Table 1 below (the unlisted parts are the same as those of Embodiment 1).

[0068] Comparative Examples 1-4

[0069] The specific raw materials, preparation parameters, isolation membrane parameters and properties of the other comparative examples are shown in Table 2 below (the unlisted parts are the same as those of Example 1).

[0070] The performance tests were performed on the diaphragms prepared in the examples and comparative examples. The specific test methods are as follows:

[0071] Thermal shrinkage: Tested in accordance with the method specified in GB / T12027-2004.

[0072] Peel strength: Use a 2.5cm×30cm mold to cut the sample, stick it flatly on a short steel ruler with double-sided tape, roll it back and forth three times with a roller, peel off 1cm manually and clamp it on a tensile testing machine for a 180° test. The tensile speed is 50mm / min, and the average of the three measurements is taken.

[0073] The increase in air permeability per unit coating thickness after hot pressing: Use a 10cm×10cm mold to cut 3 groups of samples, and test the air permeability of the diaphragm according to the requirements of JIS8117-2009, and record them as A1, A2, A 3, The cut diaphragm is hot pressed under the conditions of temperature 90℃ and pressure 4Mpa. After hot pressing, the air permeability of the diaphragm is tested according to the requirements of JIS8117-2009, which are recorded as the air permeability of the diaphragm after hot pressing A4, A5, A6. The air permeability increment after hot pressing is recorded as (A4+A5+A6-A1-A2-A3) / 3. The ratio of the air permeability increment after hot pressing to the thickness of the ceramic coating is the air permeability increment per unit coating thickness after hot pressing.

[0074] Table 1 Raw materials, preparation parameters and evaluation items of Examples 1-4

[0075]

[0076] Table 2 Raw materials, preparation parameters and evaluation items of comparative examples 1-4

[0077]

[0078] As can be seen from the table above, in Examples 1-4, the coverage of the organic film after hot pressing is less than 5%, the increase in air permeability per unit coating thickness of the diaphragm after hot pressing is ≤15s / 100cc, and the peel strength after hot pressing is ≥20gf / 15mm, showing good ion transmission performance and peeling performance after hot pressing. By controlling the etherification degree of the polymer, the number average molecular weight of the polymer, the thermal solubility ratio of the polymer, the thermoelastic recovery modulus of the polymer, the content of each component in the slurry, the proportion of the polymer added in batches, the grinding machine speed, the feed pump speed and the ratio of the feed pump speed to the grinding machine speed, and the process control during the coating process, a diaphragm with excellent peel strength and low air permeability increase after hot pressing was prepared.

[0079] In contrast, in Comparative Examples 1-3, due to changes in process control conditions, the prepared diaphragms have more sol precipitation after hot pressing, poor air permeability after hot pressing, and low peel strength, which affects the ion transmission and coating adhesion performance.

[0080] The battery separator provided by the present invention is not limited to being prepared by the preparation method provided by the present invention, and the battery separators in accordance with the present invention obtained by other methods should all fall within the protection scope of the claims of the present invention.

[0081] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.

Claims

1. A ceramic coated diaphragm, comprising a substrate layer and a ceramic coating, wherein the ceramic coating comprises ceramic particles, a binder polymer and an organic high molecular polymer, characterized in that: Under hot pressing conditions of 90°C and 4MPa, an organic film is formed on the surface of the ceramic coating after hot pressing, the coverage of the organic film is 0-5%, the value-added permeability per unit coating thickness after hot pressing is 0-15s / 100cc / μm, and the peel strength after hot pressing is above 20gf / 15mm; The substrate layer is a polyolefin base film not coated with a coating; The ceramic coating comprises 82-99 parts by weight of inorganic ceramic particles, 1.5-7 parts by weight of a binder polymer and 0.1-1.5 parts by weight of an organic high molecular polymer; The organic high molecular polymer is a polysaccharide natural high molecular compound and / or a cellulose semi-synthetic high molecular compound; The particle size D50 of the ceramic particles is 0.01 μm-2 μm; The binder polymer comprises one or more of styrene-butadiene rubber, acrylic resin, polyvinyl alcohol, polyacrylonitrile, polyvinylidene fluoride, polyethylene oxide, polytetrafluoroethylene, copolymers of acrylic acid and its derivatives, and copolymers of acrylamide and its derivatives; The cellulose semi-synthetic polymer compound has an etherification degree of 0.5-1.2 and an average number average molecular weight of 75000-95000; The characterization method of organic film coverage is as follows: the membrane is photographed at a magnification of 10k under hot pressing conditions at a temperature of 90°C and a pressure of 4MPa, and the total membrane area S within the field of view is calculated using Image software. 总 and the area covered by the film S 胶膜 , S 胶膜 / S 总 For coverage.

2. The ceramic coated diaphragm according to claim 1, characterized in that: The thickness of the substrate layer is 1-30 μm.

3. The ceramic coated diaphragm according to claim 1, characterized in that: The thickness of the ceramic coating is 0.5-10 μm.

4. The ceramic coated diaphragm according to claim 1, characterized in that: The binder polymer is polyvinylidene fluoride and / or acrylic resin.

5. The ceramic coated diaphragm according to claim 1, characterized in that: The hot melt ratio of the organic high molecular polymer at a mass concentration of 4% is below 20%, and the hot melt ratio is: (initial viscosity-viscosity after heating) / initial viscosity.

6. The method for preparing the ceramic coated diaphragm according to any one of claims 1 to 5, comprising: applying a ceramic coating slurry to the surface of at least one side of a substrate layer to obtain a substrate layer coated with a ceramic coating, and drying the substrate layer coated with a ceramic coating to obtain a ceramic coated diaphragm, characterized in that: The method for preparing the ceramic coating slurry comprises: Adding organic high molecular polymer powder into the solvent in two batches to obtain thickener slurry, wherein the mass ratio of the organic high molecular polymer powder before and after is 2:5-2:3; adding ceramic particles into a solvent to obtain a ceramic particle slurry; Mixing the thickener slurry and the ceramic particle slurry to obtain a thickening slurry; Below 65°C, the thickening slurry is conveyed to the grinder by a feed pump, and the semi-finished slurry is obtained by grinding the grinder. The grinding machine speed is 500-800rpm, the pick bead diameter is 500-800mm, the feed pump speed is 600-1000rpm, and the feed pump speed to grinder speed ratio is 1.1-1.6; After the temperature of the semi-finished product slurry returns to room temperature, a binder polymer and a wetting agent are added, and the mixture is evenly mixed to obtain a ceramic coating slurry; During the coating process, the size of the scraper leakage accounts for 40-50% of the scraper size, and the angle of the scraper and the angle of the cover plate are maintained at 0-45°. The tension applied to the base film per unit thickness and unit width is 2.5-5 N / m / μm. During the coating process, the ratio of the coating roller speed to the coating vehicle speed is between 0.8-1.2; The drying process controls the oven temperature to 50-80°C, the pressure inside the oven to 0-0.03Mpa, the oven temperature is heated in sections, and the temperature difference between two adjacent sections of the oven is ≤5°C.

7. The method for preparing a ceramic coated diaphragm according to claim 6, characterized in that: The pH value of the ceramic coating slurry is 7-11; the viscosity is 5-200 mpa·s; and the volume average particle size D50 of the ceramic coating slurry is 0.01-2.5 μm.

8. A secondary battery, characterized in that: Comprising the ceramic coated diaphragm according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Adhesive polymer-coated lithium ion battery diaphragm and preparation method thereof

    CN108305977A

  • Battery diaphragm and preparation method thereof

    CN118073766A

Cited By

  • Diaphragm coating material capable of being quickly bonded with pole piece as well as preparation method and application of diaphragm coating material

    CN120657373A

  • A separator coating material rapidly bonded with pole pieces, and a preparation method and application thereof

    CN120657373B